2004
DOI: 10.1046/j.1399-0012.2003.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated interferon α‐2b plus ribavirin in the treatment of post‐liver transplant recurrent hepatitis C

Abstract: Treatment of recurrent HCV infection with combination of IFN or PEG-IFN and RBV produced an on-therapy VR in 29% and BR in 65% of patients. Hematologic toxicity and dose modifications were frequent. Our experience with antiviral therapy for HCV post-OLT remains disappointing but PEG-IFN + RBV appears to produce VR in a sizable portion of IFN + RBV non-responders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
69
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 25 publications
9
69
1
1
Order By: Relevance
“…The over 3 year survival in five of these subjects indicate that although some co-infected patients may develop a rapid course of recurrent hepatitis C after LTx, there is a subset of patients who experience a less aggressive clinical course of HCV infection, although there were no predictors of such outcomes. It is also noteworthy that the overall VR rate to interferon-a and ribavirin therapy in coinfected patients (40%) is similar to response rates reported in the nonHIV population (39)(40)(41). In addition, our observation was that coinfected patients as well as non-HIV patients tolerated HCV treatment.…”
Section: Discussionsupporting
confidence: 84%
“…The over 3 year survival in five of these subjects indicate that although some co-infected patients may develop a rapid course of recurrent hepatitis C after LTx, there is a subset of patients who experience a less aggressive clinical course of HCV infection, although there were no predictors of such outcomes. It is also noteworthy that the overall VR rate to interferon-a and ribavirin therapy in coinfected patients (40%) is similar to response rates reported in the nonHIV population (39)(40)(41). In addition, our observation was that coinfected patients as well as non-HIV patients tolerated HCV treatment.…”
Section: Discussionsupporting
confidence: 84%
“…The best results were obtained with pegylated interferon (PEG-IFN) alfa in combination with ribavirin, with higher SVR rates compared to IFN or ribavirin monotherapies. 93 One of the main problems is to find the individual balance between tolerable and manageable side effects and maintain therapy over the whole time of treatment to maximize the number of SVR and minimize the number of relapsers.…”
Section: Therapymentioning
confidence: 99%
“…[93][94][95][96]98,99,102,105,106,109,110,127,145,146 Most published studies are uncontrolled trials with a high variability in patient selection, and type and timing of antiviral therapy. Rates of SVR have been less than those achieved in the nontransplant setting.…”
Section: Peg-ifn Plus Ribavirinmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination therapy in liver transplant patients may be associated with frequent and severe adverse events, including the frequent need for erythropoietin and/or filgrastim. [26][27][28][29] All patients in the present study required supportive treatment with erythropoietin and/or filgrastim. The frequency of treatment discontinuation because of adverse events was 39% in the present study, higher than 16% reported in immunocompetent subjects with significant severity.…”
mentioning
confidence: 99%